Prognostic markers and response to vandetanib therapy in sporadic medullary thyroid cancer patients. Issue 3 (September 2016) - Tiedje, Vera; Ting, Saskia; Walter, Robert Fred; Herold, Thomas; Worm, Karl; Badziong, Julia; Zwanziger, Denise; Schmid, Kurt Werner; Führer, Dagmar
Abstract : Objective: Medullary thyroid carcinoma (MTC) occurs sporadically in 75% of patients. Metastatic disease is associated with significantly poorer survival. The aim of this study was to identify prognostic markers for progressive MTC and oncogenic factors associated with response to vandetanib therapy. Design and methods: Clinical courses of 32 patients with sporadic MTC ( n =10 pN0cM0, n =8 pN1cM0, n =14 pN1cM1) were compared with genetic profiles of the patients' primary tumour tissue. Analysis for RET proto-oncogene mutations was performed by Sanger sequencing and next-generation sequencing (NGS). The mRNA expression (mRNA count) of 33 targets was measured by nCounter NanoString analysis. Results: Somatic RET mutations occurred in 21/32 patients. The RET918 mutation was found in 8/14 pN1cM1 patients. BRAF ( P =0.019), FGFR2 ( P =0.007), FGFR3 ( P =0.044) and VEGFC ( P =0.042) mRNA expression was significantly lower in pN1cM0/pN1cM1 compared with pN0cM0 patients, whereas PDGFRA ( P =0.026) mRNA expression was significantly higher in pN1cM0/pN1cM1 when compared with pN0cM0 patients. Among the 10/32 vandetanib-treated patients, 5 showed partial response (PR), all harbouring the RET918 mutation. mRNA expression of FLT1 ( P =0.039), FLT4 ( P =0.025) and VEGFB ( P =0.042) was significantly higher in therapy responders. Conclusions: In this study, we identified molecular markers in primary tumour tissue of sporadic MTC associated with the development of metastasis (both lymph node and organ metastasis) as well as response to vandetanib therapy.